2010
DOI: 10.1016/j.jare.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in fruits and their processed products: Analysis, occurrence and health implications

Abstract: Mycotoxins are secondary metabolites of filamentous fungi that occur naturally in food and feed. The presence of these compounds in the food chain is of high concern for human health due to their properties to induce severe toxicity effects at low dose levels. The contamination of fruits with mycotoxins has not only caused health hazards but also resulted in economic losses, especially for exporting countries. The mycotoxins most commonly found in fruits and their processed products are aflatoxins, ochratoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(130 citation statements)
references
References 76 publications
2
113
0
4
Order By: Relevance
“…They were also stable in spiked white wine for almost 8 days at room temperature. ATX-1 contents were stable when added to apple juice for up to 27 days at room temperature [10]. Overall, some Alternaria toxins remain difficult to degrade or decontaminate in fruits and their processed products.…”
Section: Stability Of Alternaria Mycotoxins the Stability Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…They were also stable in spiked white wine for almost 8 days at room temperature. ATX-1 contents were stable when added to apple juice for up to 27 days at room temperature [10]. Overall, some Alternaria toxins remain difficult to degrade or decontaminate in fruits and their processed products.…”
Section: Stability Of Alternaria Mycotoxins the Stability Ofmentioning
confidence: 97%
“…In the last decade, Ostry [1], Scott et al [9], and Fernández-Cruz et al [10] have studied the occurrence of the major Alternaria mycotoxins: AOH, AME, and TEN. However, food-relevant Alternaria species are able to produce many more metabolites including that known as emerging Alternaria mycotoxins described as potentially hazardous.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that OTA at cell level outcomes in expanded oxidative stress and abnormal state of the poison in people causing "Balkan endemic nephropathy". Numerous nations over the globe have set regulatory levels for the usage of OTA depending on the food commodities consumed [8,10]. Among all the countries, Europe is known to be a prolific consumer of the OTA-contaminated foods and the European Union has fixed the amount of OTA to be permitted in the food items which is 5ppb for crude grains, 2ppb for wines and 0.5ppb for child nourishments (Commission Regulation No.…”
Section: Introductionmentioning
confidence: 99%
“…They are disease and death causing metabolites to humans and animals (Bennett & Klich, 2003). Mycotoxins producing species colonize agricultural products during crop growth, harvesting, storage or even in processing (Fernandez-cruz, Mansilla & Tadeo, 2010). Their occurrence is influenced interdependently by physical, biological and chemical factors (Milani, 2013;Milicevic, Nesic & Jaksic, 2015).…”
Section: Introductionmentioning
confidence: 99%